Proprietary Estoppel: an italian case law perspective - Vagni, Laura (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
In the English system, the doctrine of proprietary estoppel prevents a legal owner from acting in an unconscionable manner to the detriment of a reliable claimant. A proprietary estoppel could give rise to a proprietary right of the claimant. Italian law does not recognise a similar doctrine nor does Italian property law seem compatible with it. Nevertheless, in some recent cases, the courts protected the claimant’s reasonable reliance, preventing the legal owner from acting in contradiction with his/her own previous conduct (according to the maxim venire contra factum proprium nemo potest). This paper analyses these judicial decisions, and evaluates when and how the claimant’s reliance is protected.